2021
DOI: 10.1101/2021.04.15.440004
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Computationally prioritized drugs inhibit SARS-CoV-2 infection and syncytia formation

Abstract: New affordable therapeutic protocols for COVID-19 are urgently needed despite the increasing number of effective vaccines and monoclonal antibodies. To this end, there is increasing attention towards computational methods for drug repositioning and de novo drug design. Here, we systematically integrated multiple data-driven computational approaches to perform virtual screening and prioritize candidate drugs for the treatment of COVID-19. From the set of prioritized drugs, we selected a subset of representative… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 98 publications
(84 reference statements)
0
1
0
Order By: Relevance
“…The strategy of drug repurposing has been used as a method of searching novel treatments for virus-related diseases ( Dyall et al, 2014 ; Mercorelli et al, 2018 ; Serra et al, 2021 ). A pre-clinical study has shown that the antidepressant drugs, such as sertraline, paroxetine, and clomipramine, can reduce the Zaire Ebola virus (EBOV) entry to target cells ( Johansen et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The strategy of drug repurposing has been used as a method of searching novel treatments for virus-related diseases ( Dyall et al, 2014 ; Mercorelli et al, 2018 ; Serra et al, 2021 ). A pre-clinical study has shown that the antidepressant drugs, such as sertraline, paroxetine, and clomipramine, can reduce the Zaire Ebola virus (EBOV) entry to target cells ( Johansen et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%